2016
DOI: 10.1080/22201181.2016.1154290
|View full text |Cite
|
Sign up to set email alerts
|

The United Kingdom National Audit Projects: a narrative review

Abstract: The Royal College of Anaesthetists' National Audit Project (NAP) programme has been running in its current form since 2006. Since NAP3 was commissioned the NAPs have examined rare but important complications of anaesthesia and related subspecialties. The topics covered include major complications of central neuraxial block (NAP3), major complications of airway management in hospitals (NAP4) and accidental awareness during general anaesthesia (NAP5). NAP6 is currently studying severe perioperative anaphylaxis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The National Audit Projects are a series of service evaluations examining major complications related to anaesthesia, run by the Royal College of Anaesthetists (RCoA). 7 The Sixth National Audit Project (NAP6) is designed to prospectively examine quantitative and qualitative aspects of severe perioperative anaphylaxis. NAP6 comprises four components: a baseline survey of anaesthetists; a survey of specialist allergy clinics; a year-long, anonymized case-reporting phase; and lastly a survey of anaesthetic activity and exposure to potential perioperative allergens.…”
mentioning
confidence: 99%
“…The National Audit Projects are a series of service evaluations examining major complications related to anaesthesia, run by the Royal College of Anaesthetists (RCoA). 7 The Sixth National Audit Project (NAP6) is designed to prospectively examine quantitative and qualitative aspects of severe perioperative anaphylaxis. NAP6 comprises four components: a baseline survey of anaesthetists; a survey of specialist allergy clinics; a year-long, anonymized case-reporting phase; and lastly a survey of anaesthetic activity and exposure to potential perioperative allergens.…”
mentioning
confidence: 99%
“…5e10 An important feature of the NAPs has been the extensive engagement of anaesthetists throughout the UK (and Ireland in the case of NAP5), and the promotion of multidisciplinary and crossorganisational collaborations. 11 Towards the end of the last millennium, a strong emphasis emerged in the UK on the conduct of clinical audit projects in medical practice. This focus on audit was occurring concurrently with major structural changes in medical training programs, under the banner of Calman and other reforms.…”
mentioning
confidence: 99%
“…For the last four NAPs, three general processes were conducted. 11 First, a baseline national survey was sent to all anaesthetists in the UK to establish practices and knowledge. This step had an important benchmarking role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It remains an important challenge for the NAP programme to identify whether these projects have led to demonstrable change in practice, and more importantly improvements in patient safety . A survey in 2011 identified that within a year of publication of NAP3, half of hospitals had changed information provided to patients and one quarter had changed clinical practices .…”
mentioning
confidence: 99%